Implementasi Konsep Taat Kepada Kedua Orang Tua dalam QS. Luqman Ayat 15 : (Telaah dalam Perspektif Kitab Tafsir Ibnu Katsir) - Nur Fadhilah; Muhammad Qinthar Rahman; Ahmad Syarifuddin (Ta’wiluna: Jurnal Ilmu Al-Qur'an, Tafsir dan Pemikiran Islam, 2024)
The concept of obeying children to parents through the holy verses of the Koran QS. Luqman verse 15 is an in-depth study exploring the meaning and wisdom contained in the Koran, the holy book of Islam. In this writing, the author highlights the importance of understanding the concept of obedience to parents through in-depth reflection on the holy text of the Qur'an, where the Qur'an becomes a means of understanding the concept of obedience contained therein. This study covers several key elements, including the main concepts in the Koran, namely the Islamic view of the concept of obedience to parents, morality and morals. In the process, the author highlights universal values ​​such as compassion, wisdom, justice and piety which are reflected in the teachings of the Koran. This study also explores the ways in which the Qur'an provides guidance on various aspects of life, including ethical, social, familial and spiritual. Apart from that, this writing emphasizes how the Qur'an answers the explanation of the concept of obedience to QS. Luqman verse 15 and how to implement it in everyday life. This study is expected to provide better insight into the values, principles, goals of obedient behavior in the Islamic view, as well as expand in-depth thinking about how the Koran can guide humans in matters of obeying parents in their life in the world.